Respuesta :

Answer:

A.   y = 9(x +1/2)^2 - 13/4.

Step-by-step explanation:

y = 9x^2 + 9x - 1

y = 9(x^2 + x) - 1

y = 9 [ (x + 1/2)^2 - 1/4] - 1

y = 9 (x + 1/2)^2  - 9/4 - 1

y = 9(x +1/2)^2 - 13/4.

Answer: First Option

[tex]y = (x+\frac{1}{2}) ^ 2 -\frac{13}{4}[[/tex]

Step-by-step explanation:

For a quadratic function of the form:

[tex]y = ax ^ 2 + bx + c[/tex]

The vertex form of the equation is:

[tex]y = (x-h) ^ 2 + k[/tex]

Where the vertex is the point (h, k) and [tex]h =-\frac{b}{2a}[/tex]

In this case the equation is: [tex]y=9x^2+9x-1[/tex]

So:

[tex]a=9\\b=9\\c=-1[/tex]

Therefore:

[tex]h =-\frac{9}{2*(9)}[/tex]

[tex]h =-\frac{1}{2}[/tex]

[tex]k=9(-\frac{1}{2})^2+9(-\frac{1}{2})-1\\\\k=-\frac{13}{4}[/tex]

Finally the equation in vertex form is:

[tex]y = (x+\frac{1}{2}) ^ 2 -\frac{13}{4}[[/tex]